2016
DOI: 10.1080/0361526x.2016.1153336
|View full text |Cite
|
Sign up to set email alerts
|

Troubleshooting Electronic Resources with ILL Data

Abstract: RecorderTroubleshooting electronic resource linking issues can seem to be an insurmountable task-so many resources, so little time. Using interlibrary loan (ILL) data on requests for materials available online, the electronic resources staff at the Samford University Library detected problems with the implementation of their new link resolver. This data also provided a window into some systemic issues within the metadata of certain sources and the link resolver knowledgebase. In addition to helping us improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…12 Taking a slightly different approach, Ashmore and Macauly of Samford University analyzed unfilled interlibrary loan (ILL) requests to detect patterns. 13 As a result, workflow improvements implemented included increased access to ILLIAD, wherein librarians could download reports into Excel for further analysis, rather than relying on e-mail chains. The study also identified groups who may need additional library instruction and improved collaboration among the different library departments.…”
Section: Benefits To Mining Troubleshooting Datamentioning
confidence: 99%
See 2 more Smart Citations
“…12 Taking a slightly different approach, Ashmore and Macauly of Samford University analyzed unfilled interlibrary loan (ILL) requests to detect patterns. 13 As a result, workflow improvements implemented included increased access to ILLIAD, wherein librarians could download reports into Excel for further analysis, rather than relying on e-mail chains. The study also identified groups who may need additional library instruction and improved collaboration among the different library departments.…”
Section: Benefits To Mining Troubleshooting Datamentioning
confidence: 99%
“…Ashmore and Macauly deemed the project successful with a number of benefits, and that "this process was a service opportunity offering a good way to establish positive relationships with users by saving their time." 14 Considering the many service benefits that are demonstrated in the literature, Samples and Healy were straightforward in their own recommendation: "Librarians should take the time outside of troubleshooting to mine their own data regarding access failure to improve electronic resource troubleshooting workflows." 15 Likewise, perhaps Wright elucidated the benefits of analyzing troubleshooting data the most robustly: "With enough data gathered through systems like Footprints and shared with both vendors and other institutions, libraries stand poised to improve the functionality of e-resources, not just for their own patrons, but for patrons everywhere."…”
Section: Benefits To Mining Troubleshooting Datamentioning
confidence: 99%
See 1 more Smart Citation